2022
DOI: 10.2460/javma.20.09.0498
|View full text |Cite
|
Sign up to set email alerts
|

Excisional biopsy and radiotherapy for management of an olfactory neuroblastoma in an axolotl (Ambystoma mexicanum)

Abstract: CASE DESCRIPTION A 4-year-old sexually intact male leucistic axolotl (Ambystoma mexicanum) was presented with a 2-week history of dysrexia and difficulty swallowing. CLINICAL FINDINGS Physical examination revealed a 1-cm-diameter intraoral mass on the rostral aspect of the palate and swelling of the left nasal fossa. Local invasion into the left nasal fossa was suspected during oral examination. The lesion was marginally excised, and an incompletely excised olfactory neuroblastoma was diagnosed histologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Despite the cancer resistance, up to date, there have been few cases reported in axolotl associated with carcinoma. In 1980, melanophoromas were detected in the skin samples of 2 axolotl, 117 cutaneous mastocytomas have been reported in 18 axolotls aged about 11–17 years, 118 and olfactory neuroblastoma cases were observed 119 and even treated with radiotherapy 120 . Furthermore, it has been shown that axolotl oocyte extracts (AOE) are able to reprogram breast cancer cells via DNA demethylation, re‐activation of silenced tumor suppressors expressions, removal of repressive histone marks on tumors suppressors' promoters, reduction of cancer cell and tumor growth in mouse xenografts 121 (Figure 4).…”
Section: Low Cancer Incidence Of Axolotl Offers Opportunities To Util...mentioning
confidence: 99%
“…Despite the cancer resistance, up to date, there have been few cases reported in axolotl associated with carcinoma. In 1980, melanophoromas were detected in the skin samples of 2 axolotl, 117 cutaneous mastocytomas have been reported in 18 axolotls aged about 11–17 years, 118 and olfactory neuroblastoma cases were observed 119 and even treated with radiotherapy 120 . Furthermore, it has been shown that axolotl oocyte extracts (AOE) are able to reprogram breast cancer cells via DNA demethylation, re‐activation of silenced tumor suppressors expressions, removal of repressive histone marks on tumors suppressors' promoters, reduction of cancer cell and tumor growth in mouse xenografts 121 (Figure 4).…”
Section: Low Cancer Incidence Of Axolotl Offers Opportunities To Util...mentioning
confidence: 99%
“…11,12,23 Axolotls can be affected by a variety of diseases, including gastrointestinal (e.g., foreign bodies, constipation, duodenal mucosal hyperplasia, gastric prolapse), urogenital (e.g., testicular tumor, perivesical abscess), and cardiac conditions (e.g., necrotizing myocarditis), as well as neoplasia and buoyancy disorders. 10,19,22,26,28,29,36,3840 All of these pathologies could be diagnosed using ultrasonographic examination, knowing the aspect of healthy coelomic organs. Axolotls are studied for their regenerative abilities, but diagnostic imaging of their anatomy remains poorly described.…”
Section: Introductionmentioning
confidence: 99%